Toda trabalhada na wi-fi: cotidiano travesti em trajetórias digitais - Machado, Alisson (2019)
This study aims to investigate the ways in which travestis appropriate the Internet in their everyday lives, through the mapping and observation of the digital trajectories of the research interlocutors. The development of the research is anchored in an ethnographic perspective, considering the possibilities of dialogue between the areas of communication and anthropology, reflecting on the consumption practices of digital media, especially the social network site Facebook, but also other apps used by them, paying attention to the transits and transgressions established with the other dimensions of social life. The fieldwork was mobilized by participant observation in short-term or interim-length meetings (due to the seasonal regime that characterizes the routines of some of them that are constantly moving between cities, because their work in prostitution) and by participant observation with some interlocutors that live in the city of Santa Maria, Rio Grande do Sul, Brazil. Based on a theoretical-conceptual approach to the use of digital media, the research identifies and interprets some cultural genres of the Internet uses and the ways in which digital media interact in the elaboration of sociocultural and sociocorporific experiences of travesti everyday life. The research understands that, as well as other social network sites and apps, Facebook has certain configurations and regulations that allow and potentiate certain actions, or impose constraints once their actions are organized in a preformulated model of dispositions. In addition, the contexts of interaction observed are marked by precariousness and social vulnerability, as well as by different manifestations of violence and transphobia expressed through regulations of the cisgender and heterosexual norms in force in society. However, the observed cultural genres point to a work of inventiveness that elaborates ruptures regarding the more hegemonic social regulations and ways of disputing the senses by which their experiences are interpreted. In the same way, the research points out different practices that are established from the digital networks, that focus on the forms of management and organization of the sociabilities; on the dynamics and interactions that are singularized by the work in prostitution and by the economy of the erotic exchanges and the desire and; on the religious experiences articulated in the interface with the digital technologies. The research concludes that the use of digital social networking sites and other applications that constitute the digital trajectories of the interlocutors are organized by different regimes in which the boundaries between the public and private dimensions of social life ends up being negotiated, as well as indicates how intimacy is stressed as much as being a dissident element of social norms, as driven by dispositions that seek the ordering of their realities.